Botswana : Report on Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2002)
This Report on the Observance of Standards and Codes data module provides a review of Botswana's data dissemination practices against the IMF's General Data Dissemination System, complemented by an in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. All three of Botswana's statistics producing agencies have a legal and institutional framework that supports statistical quality and demonstrate an awareness of quality as the cornerstone of statistical work. All three agencies also demonstrates professionalism and provide ethical guidelines to their staff.